Implementation of Buzz Group Strategy Learning to Improve Students' Understanding of the Virtues of Giving to the Lessons of the Qur'an Hadits in Class VI MI Negeri 3 Academic Years 2022/2023 - Nurudin Nurudin (International Journal Labs, 2023)
This research is based on the following problems: (a) Does Buzz Group learning affect the learning outcomes of the Qur'an Hadith in Class VI Students? (b) How high is the level of mastery of the subject matter of the Qur'an Hadith with the application of the Buzz Group learning method to Class VI Students? The objectives of this study are: (a) To reveal the influence of Buzz Group learning on the learning outcomes of the Qur'an Hadith in Class VI Students. (b) Want to know how far the understanding and mastery of the subject of the Qur'an Hadith after the application of Buzz Group learning to Class VI Students This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was Class VI students. The data obtained are in the form of formative test results and, observation sheets for teaching and learning activities. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (63%), cycle II (76%), cycle III (100%). The conclusion of this research is that the Buzz Group method can have a positive effect on the learning motivation of Class VI students, and this learning model can be used as an alternative to the Qur'an Hadith.